(untitled) (Research, Society and Development, 2021)
The work presented here has its genesis in studies developed for a dissertation research, within the scope of the master’s course in Brazilian Education at the Federal University of Ceara (UFC), carried out from 2015 to 2017, by the main author. That said, this article was built from the rescue of the aforementioned theme, and is configured as an exploratory research, with a qualitative approach, whose theoretical basis was focused, mainly, on the writings of Bernard Charlot and on the educational legal frameworks. We had as central objectives to present and discuss changes suffered by the public basic school over the years, at the level of Brazil, and its impacts on education; as well as reflecting on the challenges faced by the school, considering their contexts and subjects, especially teachers, in the search for a more plural society, based on a citizen formation. We conclude that, within the constantly transformed social dynamics - in which the school we are referring to is found, with its new requirements, its new type of student and its new teaching assignments - despite what the legal documents establish, about a citizen formation, there are many paths and contradictions in search of an education that enables the promotion of a more plural society.